Growth, Biomass and Nutrient Production of Brown Midrib Sorghum Mutant Lines at Different Harvest Times - Sriagtula, R.; Karti, P.D.M.H.; Abdullah, L.; Supriyanto; Astuti, D.A. (Pakistan Journal of Nutrition, 2016)
Brown midrib sorghum (BMR) is a potential crop as forage because of lower lignin content than that of non-BMR sorghum. The aim of this research was to observe the growth and production of brown midrib sorghum mutant lines at different harvest times. This research was conducted at SEAMEO BIOTROP, Bogor, Indonesia using factorial in completely randomized block design (7 x 3) with three replicates. The first factor was the BMR sorghum mutant lines of Patir 3.1 (non-BMR/control), Patir 3.2, Patir 3.3, Patir 3.4, Patir 3.5, Patir 3.6 and Patir 3.7, the second factor was the harvest times (flowering, soft and hard dough phases). Measurement on agronomic parameters were fresh and dry matter biomass production, plant height, stem diameter, leaf width length and ratio of leaves, stems and panicles. While nutrient parameters were crude protein, crude fiber, ash dan crude fat production. Analysis of variance followed by Duncan Multiple Range Test (DMRT) was done. The results showed that the BMR of P 3.7 and P 3.2 produced the highest fresh and dry matter production among the BMRs, but their dry matter production were lower than P 3.1 (control). Harvesting at hard dough phase produce the highest fresh and dry matter production and as well as produced the highest crude protein, ash and crude fat production (p